Объяснение:
1) Mg(NO3)2 + 2KOH = Mg(OH)2 + 2KNO3
Mg(2+) + 2NO3(-)+ 2K(+)+ 2OH(-) = Mg(OH)2 + 2K(+)+ 2NO3(-)
Mg(2+) + 2OH(-) = Mg(OH)2
2) AlCl3 + 3NaOH = Al(OH)3 + 3NaCl
Al(3+) + 3Cl(-)+ 3Na(+) + 3OH(-)= Al(OH)3 +3Na(+)+ 3Cl(-)
Al(3+) + 3OH(-)= Al(OH)3
3) H2SO4 + CaCO3 = CaSO4 + CO2 + H2O
2H(+)+ SO4(2-) + CaCO3 = CaSO4 + CO2 + H2O
4) Na2SO3 + 2HCl = 2NaCl + SO2 + H2O
2Na(+) + SO3(2-) + 2H(+) + 2Cl(-) = 2Na(+)+ 2Cl(-) + SO2 + H2O
SO3(2-) + 2H(+)= SO2 + H2O
5) Al(OH)3 + 3HNO3 = Al(OH)3 + 3H2O
Al(OH)3 + 3H(+)+ 3NO3(-) = Al(OH)3 + 3H2O
Ca(OH)2 + 2HCl = CaCl2 + 2H2O
2HCl + CaO = CaCl2 + H2O
Zn + 2HCl = ZnCl2 + H2
Mg + 2HCl = MgCl2 + H2
CuSO4 + Fe = FeSO4 + Cu
CuSO4 + Ca(OH)2 = Cu(OH)2 + CaSO4
CuSO4 + Zn = ZnSO4 + Mg
CuSO4 + Mg = MgSO4 + Cu
CuSO4 + 5H2O = CuSO4·5H2O
3Fe + 4H2O = Fe3O4 + 4H2
Zn + H2O = ZnO + H2
Mg + H2O = MgO + H2
CaO + H2O = Ca(OH)2
Zn + Ca(OH)2 = CaZnO2 + H2
Zn + Ca(OH)2 + 2H2O = Ca[Zn(OH)4] + H2